Trasformazioni recenti della geografia della produzione: il reshoring e la sua diffusione nel contesto italiano - Paola Savi (Bollettino della Società Geografica Italiana, 2020)
Manufacturing reshoring, or the company decision to bring offshoring production back to the home country, has recently received a great attention in developed countries as a possible way to re-industrialization. The paper investigates the main features, the drivers and the possible impact of reshoring as well as its spreading to Italy, as they emerge from extant literature and empirical evidence. A short focus on a group of Italian industrial districts will be proposed at the end of the paper. Up to now, available empirical evidence doesn’t support strong conclusions about the positive impact of reshoring on developed countries, particularly regarding job creation. Anyway, these limitations could open to future empirical research in Economic Geography, particularly regarding the role of reshoring in local production systems.